1977
DOI: 10.1139/m77-158
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the antiherpesvirus drug 5-methoxymethyl-2′-deoxyuridine on the humoral immune response in vivo

Abstract: 5-Methoxymethyl-2'-deoxyuridine (MMUdR), a drug with potent antiviral activity in vitro against Herpes simplex virus, was investigated for its immunosuppressive effects. Doses as high as 2000mg/kg given daily for 9 days were not immunosupporessive as judged by the fact that treated animals produced normal immune responses to sheep erythrocytes, Brucella bacteria, and Herpes simplex virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1979
1979
1986
1986

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In addition, some tend to have poor aqueous solubility [28]. MMUdR is a unique nucleoside antimetabolite since it has been found to be nontoxic to lymphoid functions in vitro [3] and devoid of immu nosuppressant activity in vivo [31]. The re sults of studies reported in this paper indi cate that 2 and 5% MMUdR in either PVA or ABT were effective in the treatment of herpes keratitis.…”
Section: Discussionmentioning
confidence: 83%
“…In addition, some tend to have poor aqueous solubility [28]. MMUdR is a unique nucleoside antimetabolite since it has been found to be nontoxic to lymphoid functions in vitro [3] and devoid of immu nosuppressant activity in vivo [31]. The re sults of studies reported in this paper indi cate that 2 and 5% MMUdR in either PVA or ABT were effective in the treatment of herpes keratitis.…”
Section: Discussionmentioning
confidence: 83%
“…5-Methoxymethyl-2' -Deoxyuridine 5-Methoxymethyl-2'~deoxyuridine (MMdUrd) was synthesized by BUBBAR and GUPTA (1970). MMdUrd does not appear to be immunosuppressive ROUSE et al 1977) and the basis for its selectivity and its mechanism of action are unknown. At 100 times the antiviral concentration, MMdUrd did not cause host cell toxicity .The analog was ineffective against vaccinia virus, murine cytomegalovirus, equine rhinopneumonitis, and feline pneumonitis viruses as well ).…”
Section: E-5-(2-bromovinyl)-2'-deoxyuridine (Bvdurd)mentioning
confidence: 99%
“…It is devoid of toxicity to lymphoid functions in vitro (2), is non-immunosuppressive in vivo (26), and is effective in the treatment of keratitis in animals (20 In each experiment, toxicity controls (containing test compound and medium only), cell controls (containing medium only), and virus controls (containing virus and medium only) were also run simultaneously. The percentage ofinhibition (calculated from the reduction in the number of plaques) at each concentration of the compound was determined.…”
mentioning
confidence: 99%